2016
DOI: 10.3109/10715762.2016.1162300
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine oxidase-induced hydroxyl radical production and cardiomyocyte injury during myocardial ischemia–reperfusion in rats

Abstract: To elucidate the involvement of monoamine oxidase (MAO) in hydroxyl radical production and cardiomyocyte injury during ischemia as well as after reperfusion, we applied microdialysis technique to the heart of anesthetized rats. Dialysate samples were collected during 30 min of induced ischemia followed by 60 min of reperfusion. We monitored dialysate 3,4-dihydrobenzoic acid (3,4-DHBA) concentration as an index of hydroxyl radical production using a trapping agent (4-hydroxybenzoic acid), and dialysate myoglobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…This effect was not observed by inhibition of SERT (Du et al, 2017), moreover it was similar to the effect of MAO inhibition by pargyline as we reported previously (Du et al, 2017). We have also demonstrated MAO-dependent production of hydroxyl radical in the heart during ischemia and reperfusion (Inagaki et al, 2016). These findings suggest that PMAT is involved in the MAO-dependent deleterious effects in the reperfusion-induced cellular injury (Bianchi et al, 2005;Kaludercic et al, 2011).…”
Section: Contribution Of Pmat To 5-ht Uptake During Reperfusionsupporting
confidence: 88%
“…This effect was not observed by inhibition of SERT (Du et al, 2017), moreover it was similar to the effect of MAO inhibition by pargyline as we reported previously (Du et al, 2017). We have also demonstrated MAO-dependent production of hydroxyl radical in the heart during ischemia and reperfusion (Inagaki et al, 2016). These findings suggest that PMAT is involved in the MAO-dependent deleterious effects in the reperfusion-induced cellular injury (Bianchi et al, 2005;Kaludercic et al, 2011).…”
Section: Contribution Of Pmat To 5-ht Uptake During Reperfusionsupporting
confidence: 88%
“…We have recently demonstrated that local administration of pargyline decreased the production of hydroxyl radical and myoglobin efflux as an index of myocardial cell injury in the region restricted around the dialysis fiber (12). Moreover, although fluoxetine is a selective SERT inhibitor, high-dose fluoxetine may inhibit the NE transporter at cardiac sympathetic nerve endings (25).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…These include two enzymes localized to the mitochondrial outer membrane, p66 Shc and monoamine oxidase (MAO) (118, 194, 367, 790) (Fig. 8).…”
Section: Mechanisms Underlying I/r Cell Injury and Deathmentioning
confidence: 99%
“…These enzymes normally function to oxidatively deaminate monoamine neurotransmitters and dietary tyramines, producing aldehydes and hydrogen peroxide (193, 194, 205). However, there is an emerging body of evidence indicating that MAOs also contribute to oxidative stress in cardiac I/R injury (70, 367, 408, 409, 817). …”
Section: Mechanisms Underlying I/r Cell Injury and Deathmentioning
confidence: 99%